2007
DOI: 10.1007/s11205-007-9168-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Generative Action Among Adults in Two Transitional Countries

Abstract: Generativity, Generative action, Transition, Croatia, Slovenia,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
(8 reference statements)
1
1
0
Order By: Relevance
“…In relation to the first hypothesis, results showed that older people participating in political organisations scored significantly higher on generative concern than the comparison group. These results correspond with findings from prior studies that showed a significant relationship between generative concern and a range of generative behaviours (Penezić et al 2008;Villar et al 2013), volunteering activities (Son and Wilson 2011), or different measures of social responsibility to family and community (Rossi 2001). Results of the present study show that generative concerns are also related to older people's involvement in political activities.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In relation to the first hypothesis, results showed that older people participating in political organisations scored significantly higher on generative concern than the comparison group. These results correspond with findings from prior studies that showed a significant relationship between generative concern and a range of generative behaviours (Penezić et al 2008;Villar et al 2013), volunteering activities (Son and Wilson 2011), or different measures of social responsibility to family and community (Rossi 2001). Results of the present study show that generative concerns are also related to older people's involvement in political activities.…”
Section: Discussionsupporting
confidence: 90%
“…Einolf 2014; Gruenewald et al 2012). Previous studies have shown that generative concern is positively associated with a range of generative behaviours (Penezić et al 2008;Villar et al 2013). Higher levels of generative concern have also been positively associated with volunteering (Son and Wilson 2011) and some measures of social responsibility to family and community (Rossi 2001).…”
Section: Generativity: a Multidimensional Conceptmentioning
confidence: 98%